2019
DOI: 10.5114/wo.2019.89248
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different segmentation methods on primary tumour metabolic volume assessed in 18F-FDG-PET/CT in patients with cervical cancer, for radiotherapy planning

Abstract: IntroductionGynaecological cancers, including cervical cancer, often require a multidisciplinary approach that includes external beam radiotherapy, chemotherapy, and/or surgical treatment. Biological parameters of the tumour evaluated in 18F-FDG-PET/CT are used for target volume delineation in radiotherapy planning. The choice of segmentation method may affect the assessment of metabolic tumour volume (MTV) in 18F-FDG-PET/CT.Aim of the studyTo find the optimal segmentation method for the assessment of primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…MTV together with TLG are volumetric PET parameters using a threshold-based volume of interest 43 . Since according to the current 8th TNM classification, tumour volume plays a crucial role in cancer staging, an analysis performed in a group of cancer patients is meaningful.…”
Section: Discussionmentioning
confidence: 99%
“…MTV together with TLG are volumetric PET parameters using a threshold-based volume of interest 43 . Since according to the current 8th TNM classification, tumour volume plays a crucial role in cancer staging, an analysis performed in a group of cancer patients is meaningful.…”
Section: Discussionmentioning
confidence: 99%
“…Recent cervical cancer studies have independently explored the optimal MTV thresholds [ 13 , 16 , 17 ]. Upasani et al in a study of 74 patients with stage IIB or IIIB squamous cell cervical cancer concluded that MTV 30 and MTV 35 were most optimal using tri-diameter ellipsoid based measurements of T2W MRI as the reference standard [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cegła et al assessed 30 cervical cancer patients and concluded that the MTV 35 was the closest to the MRI reference standard; however, they did not detail the method of MRI volume measurement [ 17 ]. In this study, only three thresholds were evaluated and this limited the scope of outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PET/CT imaging was done according to our study protocol in the bed position (1.3 min for one bed position) and cutting scans 5 mm thick. The optimal contouring method was obtained using the 35% SUV max (standardized uptake value) threshold and was already verified and described in our previous research [ 2 ]. To determine heterogeneity of the primary tumor area under Cumulative SUV-volume histograms the tumor heterogeneity index (AUC-CSH) was used.…”
Section: Methodsmentioning
confidence: 99%